What Influences Pensioners to Use Social Protection Services? - Lekić, Igor; Stamenković, Željka; Matejić, Bojana; Maksimović, Nataša (Medical Research, 2024)
Introduction/Aim. Ageing as a natural phase in the life of every individual and it is correlated to life changes like retirement when the active working life of a person is ending, and it is compensated with sources of income that do not have to be earned by working, called pension. The aim of this study was to analyze the use of social services among the retired population and examine factors associated with the use of social care. Material and Methods. This cross-sectional study is a secondary analysis of data collected from the research of the Union of pension holders of Serbia, that has been done on a convenient sample of retirees. An anonymous written questionnaire was designed for this specific research. Univariate and multivariate statistic regression was used to analyze factors associated with the use of social services. Results. Only 6,5% of retirees are using some social protection services. Older age, living alone, lower level of education, and not having a mobile phone or computer significantly decrease the probability of using social protection services. Also, spending time with friends and family significantly decreases the probability that a person will use some social protection services. Conclusion. Work in the aspect of health education is highly important with a high accent on spreading the knowledge about health-related, psychological and social aspects of the ageing process to overcome stereotypes, prejudices and misunderstandings of this stage of life.